Inflation Targeting and the Crisis : An Empirical Assessment - de Carvalho Filho, Irineu (IMF Working Papers; Working Paper ;, 2010)
This paper appraises how countries with inflation targeting fared during the current crisis, with the goal of establishing the stylized facts that will guide and motivate future research. We find that since August 2008, IT countries lowered nominal policy rates by more and this loosening translated into an even larger differential in real interest rates relative to other countries; were less likely to face deflation scares; and saw sharp real depreciations not associated with a greater perception of risk by markets. We also find some weak evidence that IT countries did better on unemployment rates and advanced IT countries have had relatively stronger industrial production performance. Finally, we find that advanced IT countries had higher GDP growth rates than their non-IT peers, but find no such difference for emerging countries or the full sample.